Mobilność przestrzenna ludności Polski w układzie międzyregionalnym w procesie transformacji - Kociszewski, Jerzy; Konopska-Struś, Emilia (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The aim of this paper is to evaluate mobility of the Polish inhabitants during the economy system transformation on the ground of the statistic data. As the result of this analysis some factors have been identified, that differentiate inhabitants mobility in some Polish regions. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 84-95